2021
DOI: 10.1091/mbc.e20-07-0492
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic, synthetic, and balancing interactions among tubulin missense mutations affecting neurite growth inCaenorhabditis elegans

Abstract: Mutations in tubulins affect microtubule (MT) dynamics and functions during neuronal differentiation and their genetic interaction provides insights into the regulation of MT functions. We previously used C. elegans touch receptor neurons to analyze the cellular impact of tubulin mutations and reported the phenotypes of 67 tubulin missense mutations, categorized into three classes: loss-of-function ( lf), antimorphic ( anti), and neomorphic ( neo) alleles. In this study, we isolated 54 additional tubulin allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…To study the effects of MT dynamics, we tracked EBP-2::GFP comets in the TRNs using the juIs338[mec-4p::ebp-2::GPF + ttx-3p::RFP] transgene based on a previous protocol [22]. Day-one adults were mounted with 100 nm polystyrene beads (Polysciences #00876-15; 5-fold dilution) on an agarose pad, and their PLMs were imaged for 1 min with 150-ms exposure time and 350-ms time intervals.…”
Section: Methodsmentioning
confidence: 99%
“…To study the effects of MT dynamics, we tracked EBP-2::GFP comets in the TRNs using the juIs338[mec-4p::ebp-2::GPF + ttx-3p::RFP] transgene based on a previous protocol [22]. Day-one adults were mounted with 100 nm polystyrene beads (Polysciences #00876-15; 5-fold dilution) on an agarose pad, and their PLMs were imaged for 1 min with 150-ms exposure time and 350-ms time intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Through extensive genetic screens, a large collection of mec-12 and mec-7 missense mutations (99 alleles in total) had been isolated and characterized for their effects on neurite growth ( Zheng et al, 2017 ; Lee et al, 2021 ). In addition to many loss-of-function mutants, two distinct types of gain-of-function alleles were found among the missense alleles, and they had much stronger effects on neurite growth than the deletion alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, studies of the mec-12 and mec-7 alleles also found complex genetic interactions between the tubulin mutations, including epistatic, additive, synthetic, and balancing effects ( Lee et al, 2021 ). For example, the effects of neomorphic gain-of-function mutants can be suppressed by loss-of-function and antimorphic gain-of-function mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanosensory neurons of C. elegans, responsible for gentle touch sensation, have been used to study microtubule regulation and neuronal polarization in vivo (39)(40)(41). In this study, we have identified a mutation in the muscleblind-1 gene, as a suppressor of the touch neuron developmental defect in loss of kinesin-13 family microtubule depolymerase, klp-7.…”
Section: Introductionmentioning
confidence: 99%